Conservação preventiva de acervos orgânicos na Amazônia: estudo de caso no Museu Casa das Onze Janelas e Museu de Arte de Belém do Pará - CASTRO, Tayná Mariane Monteiro de (2019)
Organic collections are the most susceptible to changes due to environmental conditions. That’s why Preventive Conservation, responsible for the deceleration of the effects caused by agents of deterioration in museological collections, is essential for the safeguarded heritage to last longer. However, there are no established standards in the bibliographies for Amazon’s particularities. Therefore, in order to contribute to the development of curatorial practices in Amazon’s collections, this work analyzes the climatization of organic collections in long term exhibition, at the Museu de Arte de Belém and the Museu Casa das Onze Janelas. The temperature and humidity of the environments were monitored for 4 months. In both analyzed institutions, there are high temperature and relative humidity levels, but the variation of these, considered the most damaging to the collections, is controlled in different ways, either through a good storage like the "Gabinete de papéis" or an air conditioning non-dependent system, with the aid of the building structure, which in both cases can maintain the good conditions of the objects. Therefore, we show that there is not a single form of conservation, and that it is possible to preserve collections as delicate as the organics in environments as adverse as the Amazon.